The privileged role of researchers in "evidence-based" policy: implications and engagement of other voices. Issue 4 (7th December 2015) - Ritter, Alison
Abstract : Purpose: – This paper starts from the familiar premise of evidence-based policy, and examines the active role that researchers play in policy development processes. The interactive nature of much research translation immediately suggests the need to consider the dynamic way in which problems come to be understood, which is explored in this paper. Furthermore, the integration of research knowledge with the knowledges of "ordinary" citizens is a key challenge. The paper aims to discuss these issues. Design/methodology/approach: – This paper represents a synthesis of recent studies conducted by the author and her colleagues along with other drug policy literature. Findings: – The interactive and dialogic processes that researchers engage with, whether as knowledge brokers or participants in elite policy development forums, have implications for how policy problems (and solutions) come to be constituted. Four perspectives and theoretical approaches are briefly outlined: research design; policy processes; problematization; and critical social sciences analyses. These offer different ways of seeing, understanding and analyzing the relationship between problems, policy solutions and the policy processes. Yet all have lessons for the ways in which research evidence and researchers constitute policy. This needs to sit alongside the role of other drug policy stakeholders – notably the "ordinary" citizen. It is argued that the elite role of research can be tempered with engagement of ordinary citizens. While it can be challenging to reconcile general public views about drugs with the evidence-base, deliberative democracy approaches may hold some promise. Originality/value: – This paper draws together a number of central themes for drug policy processes research: where the evidence-based policy paradigm intersects with participatory democracy; how problems are constituted; and the privileged role of research and researchers.